Green Electrochemistry - A Versatile Tool in Green Synthesis: an Overview - Rajendran,Susai (2016)
Green is attractive and beautiful. Green chemistry has attracted scientists and researchers from various fields. Electrolysis is considered as green electrochemistry, because electrochemical process can be stopped and controlled at any time and at any stage of the reaction. Usually water is used as the solvent. Corrosive acids are not used. Toxic chemicals are not involved. The main components of an electrolysis process are anode, cathode and electrolyte. By using suitable anodes, cathodes and medium, electrolysis has been applied in various fields. Electrolysis has been used to decolourise dyes from effluents of textile industries. The decolourisation efficiencies of various anodes, such as platinised-titanium, mild steel and aluminium in various electrolytic media, such as well water and sea water, have been evaluated and compared. The role of positive chlorine in the decolourisation process has been established. Electrolysis, in presence of a suitable reducing agent, has also been used to synthesize nanoparticles. Copper nanoparticles and silver nanoparticles have been produced by making use of reducing agents, such as sodium potassium tartrate and trisodium citrate. Various plants extracts have also been used as reducing agents. The nanoparticles synthesized by green methods have been characterized by UV-Visible absorption spectroscopy and fluorescence spectroscopy. The surface morphology of these nanoparticles has been characterized by SEM and EDS. Blue pigment that can be used in paint industry has been synthesized by green electrolysis. For this purpose, waste mild steel rod has been used, and graphite has been used as anode. The blue pigment prepared has been characterized by UV-Visible absorption spectroscopy and fluorescence spectroscopy. The surface morphology of these nanoparticles has been characterized by SEM and EDS. The blue pigment prepared is found to be in the nano range. This can be used in paint industry and also in the field of nano biosensors. By green electrolysis method, Hofmann rearrangement has been successfully effected, benzamide being the starting material. The product obtained has been diazotised and coupled with Î±-napthol and Î²-napthol to give dyes. The dyes have been characterized by UV-Visible absorption spectroscopy and fluorescence spectroscopy. Polyaniline has also been synthesized by green electrolysis process, without using expensive oxidizing agents, but using positive chloride ions generated in-situ during electrolysis, in the presence of sodium chloride solution as electrolyte. The polyaniline produced has been characterized by UV-Visible absorption spectroscopy, fluorescence spectroscopy and FTIR spectra.